Uterine contractile activity in healthy women throughout the menstrual cycle measured using a novel quantitative two-dimensional transvaginal ultrasound speckle tracking method. Issue 1 (January 2023) - Rees, Connie Odette; de Boer, Anna; Huang, Yizhou; Wessels, Blijke; Blank, Celine; Kuijsters, Nienke; Huppelschoten, Aleida; Zizolfi, Brunella; Foreste, Virginia; Di Spiezio Sardo, Attilio; Christoforidis, Nikos; van Vliet, Hubertus; et al.
Abstract: Research question: To explore normal uterine contractile function across the menstrual cycle using a novel quantitative ultrasound method. Design: This multicentre prospective observational study took place in three European centres from 2014 to 2022. Uterine contraction frequency (contractions/minute), amplitude, direction (cervix-to-fundus, C2F; fundus-to-cervix; F2C), velocity and coordination were investigated. Features were extracted from transvaginal ultrasound recordings (TVUS) using speckle tracking. Premenopausal women ≥18 years of age, with normal, natural menstrual cycles were included. A normal cycle was defined as: regular (duration 28 ± 2 days), no dysmenorrhoea, no menometrorrhagia. Four-minute TVUS were performed during the menstrual phase, mid-follicular, late follicular phase, early luteal phase and/or late luteal phase. Of the 96 recordings available from 64 women, 70 were suitable for inclusion in the analysis. Results: Contraction frequency (for the posterior wall) and velocity (for the anterior uterine wall in the F2C direction) were highest in the late follicular phase and lowest in the menstrual and late luteal phases (1.61 versus 1.31 and 1.35 contractions/min, P < 0.001 and 0.81 versus 0.67 and 0.62 mm/s, P < 0.001, respectively). No significant difference was found for contraction amplitude. Contraction coordination (simultaneous contraction of the anterior and posterior walls in the same direction) was least coordinated in the mid-follicular phase ( P = 0.002). Conclusions: This is the first study to objectively measure uterine contraction features in healthy women during the natural menstrual cycle on TVUS. Likewise, it introduces contraction coordination as a specific feature of uterine peristalsis. Differences in uterine contractility across the menstrual cycle are confirmed, with highest activity seen in the late follicular phase, and lowest in the late luteal phase.